Generalized Continua as Models for Classical and Advanced Materials - Altenbach, Holm.; Forest, Samuel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume is devoted to an actual topic which is the focus world-wide of various research groups. It contains contributions describing the material behavior on different scales, new existence and uniqueness theorems, the formulation of constitutive equations for advanced materials. The main emphasis of the contributions is directed on the following items - Modelling and simulation of natural and artificial materials with significant microstructure, - Generalized continua as a result of multi-scale models, - Multi-field actions on materials resulting in generalized material models, - Theories including higher gradients, and - Comparison with discrete modelling approaches.
1 On Strain Rate Tensors and Constitutive Equations of Inelastic Micropolar Materials -- 2 On the Modelling of Carbon Nano Tubes as Generalized Continua -- 3 Isogeometric Analysis of Gradient-Elastic 1D and 2D Problems -- 4 A Fast Fourier Transform-Based Approach for Generalized Disclination Mechanics Within a Couple Stress Theory -- 5 Some Cases of Unrecognized Transmission of Scientiﬁc Knowledge: from Antiquity to Gabrio Piola's Peridynamics and Generalized Continuum Theories -- 6 Computational Analysis of the Size Effects Displayed in Beams with Lattice Microstructures.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Materials; Solid Mechanics; Characterization and Analytical Technique; Materials Engineering